2021
DOI: 10.1038/s41598-021-83235-8
|View full text |Cite
|
Sign up to set email alerts
|

Legume-rhizobium specificity effect on nodulation, biomass production and partitioning of faba bean (Vicia faba L.)

Abstract: Greenhouse and multi-location experiments were conducted for two consecutive years to investigate the effects of rhizobium on nodulation, biomass production and partitioning of faba bean. Split-plot in randomized complete block design was used for field experiments. Treatments consisted of six rhizobium strains and three faba bean varieties. Peat carrier-based inoculant of each strain was applied at the rate of 10 g kg−1 seed. Non-inoculated plants without N fertilizer and with N fertilizer served as –N and + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 56 publications
3
25
0
Order By: Relevance
“…Overall, the field study results reveal high yield potential of faba bean cultivars and the controlled‐environment study supports the potential for a significant external contribution of N from BNF by faba bean (∼88% Ndfa). As confirmed in both studies, the amount of N 2 fixation in faba bean is dependent on the cultivar, agronomical practices (e.g., plant density, and N and P fertilization), soil properties, and the presence of appropriate rhizobia bacteria in the soil (Allito et al., 2021; Chen et al., 2018; Schubert et al., 1990; Sprent & Bradford, 1977).…”
Section: Discussionmentioning
confidence: 77%
“…Overall, the field study results reveal high yield potential of faba bean cultivars and the controlled‐environment study supports the potential for a significant external contribution of N from BNF by faba bean (∼88% Ndfa). As confirmed in both studies, the amount of N 2 fixation in faba bean is dependent on the cultivar, agronomical practices (e.g., plant density, and N and P fertilization), soil properties, and the presence of appropriate rhizobia bacteria in the soil (Allito et al., 2021; Chen et al., 2018; Schubert et al., 1990; Sprent & Bradford, 1977).…”
Section: Discussionmentioning
confidence: 77%
“…Besides, it contains sugars, dietary fibers, starch, minerals, vitamins and essential amino acids (1,2). Interestingly, leguminous pulse crops including blackgram sustain their growth by establishing a symbiotic association with Rhizobium, which fix atmospheric nitrogen in the root nodules (3)(4)(5)(6)(7). In addition to Rhizobium, AM fungi also form a symbiotic association with leguminous crops (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that inoculation of legumes with effective rhizobia can improve yields and provide a substitute for inorganic fertilizers. Research has recognized inoculation with effective and appropriate rhizobial strain is necessary to improve symbiotic nitrogen fixation and optimize faba bean productivity [72]. These authors also revealed that inoculation affects microbial community by increasing desired rhizobia strain population in the rhizosphere and for successful establishment, inoculants strain must be able to survive in the soil environment and take advantage of an ecological niche to be offered by the roots of the host plant.…”
Section: Rhizobium Inoculationmentioning
confidence: 99%
“…Therefore, symbiotic performance depends on the abundance of effective rhizobia strain and its competitiveness for nodulation. It is evident that there are diversified faba bean cultivars in Sub-Saharan Africa that are likely to be accompanied by symbiotically effective nitrogen-fixing indigenous Rhizobium strains [72].…”
Section: Rhizobium Inoculationmentioning
confidence: 99%